Recent Advances in the Removal of Organic Dyes from Aqueous Media with Conducting Polymers, Polyaniline and Polypyrrole, and Their Composites - Stejskal, Jaroslav (Polymers, 2022)
Water pollution by organic dyes, and its remediation, is an important environmental issue associated with ever-increasing scientific interest. Conducting polymers have recently come to the forefront as advanced agents for removing dye. The present review reports on the progress represented by the literature published in 2020-2022 on the application of conducting polymers and their composites in the removal of dyes from aqueous media. Two composites, incorporating the most important polymers, polyaniline, and polypyrrole, have been used as efficient dye adsorbents or photocatalysts of dye decomposition. The recent application trends are outlined, and future uses also exploiting the electrical and electrochemical properties of conducting polymers are offered.
Keywords: composites; dye adsorption; polyaniline; organic dyes; conducting polymers; photocatalytic decomposition; polypyrrole; dye removal